Evidence of exposure to henipaviruses in domestic pigs in Uganda. Issue 2 (19th January 2019) - Atherstone, Christine; Diederich, Sandra; Weingartl, Hana M.; Fischer, Kerstin; Balkema‐Buschmann, Anne; Grace, Delia; Alonso, Silvia; Dhand, Navneet K.; Ward, Michael P.; Mor, Siobhan M.
Abstract: Hendra virus (HeV) and Nipah virus (NiV), belonging to the genus Henipavirus, are among the most pathogenic of viruses in humans. Old World fruit bats (family Pteropodidae) are the natural reservoir hosts. Molecular and serological studies found evidence of henipavirus infection in fruit bats from several African countries. However, little is known about the potential for spillover into domestic animals in East Africa, particularly pigs, which served as amplifying hosts during the first outbreak of NiV in Malaysia and Singapore. We collected sera from 661 pigs presented for slaughter in Uganda between December 2015 and October 2016. Using HeV G and NiV G indirect ELISAs, 14 pigs (2%) were seroreactive in at least one ELISA. Seroprevalence increased to 5.4% in October 2016, when pigs were 9.5 times more likely to be seroreactive than pigs sampled in December 2015 ( p  = 0.04). Eight of the 14 ELISA‐positive samples reacted with HeV N antigen in Western blot. None of the sera neutralized HeV or NiV in plaque reduction neutralization tests. Although we did not detect neutralizing antibodies, our results suggest that pigs in Uganda are exposed to henipaviruses or henipa‐like viruses. Pigs in this study were sourced from many farms throughout Uganda, suggesting multiple (albeit rare) introductions of henipaviruses into the pig population. We postulate that given the widespread distribution of Old World fruit bats in Africa, spillover of henipaviruses from fruit bats to pigs in Uganda could result in exposure of pigs at multiple locations. A higher risk of a spillover event at the end of the dry season might be explained by higher densities of bats and contact with pigs at this time of the year, exacerbated by nutritional stress in bat populations and their reproductive cycle. Future studies should prioritize determining the risk of spillover of henipaviruses from pigs to people, so that potential risks can be mitigated.